Agricultural Input Uses and Rice Productivity Assessment: A Case Study in Battambang and Svay Rieng Provinces, Cambodia - Keo, Hak; Serey, Mardy; Yun, Sopheap; Srean, Pao (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the Study: The study aims to 1) assess the use of farming inputs and rice productivity in Battambang and Svay Rieng provinces, Cambodia; 2) identify the factors influencing rice productivity; and 3) predict rice productivity based on farming inputs. It seeks to provide insights into optimizing rice production and improving farmers' livelihoods. Methodology: A survey was conducted across 7 villages, 2 communes, and 2 districts in Battambang and Svay Rieng provinces, with 148 samples collected. Data were analyzed using quantitative and qualitative methods, including frequency analysis, descriptive statistics, cross-tabulation, chi-square tests, one-sample t-tests, and p-value probability. Main Findings: The study revealed that the average number of family members involved in farming was 2 (70%), and land sizes ranged from 2-4 hectares (40%). DAP was the most commonly used chemical fertilizer (66%). Land size significantly affected rice productivity (93%), followed by seed quality (86% yield increase) and pesticide use (91% yield increase). Chemical fertilizers had a near-total impact on productivity. The study recommends reducing chemical fertilizers in favor of organic alternatives for safer and higher-quality rice production. Novelty/Originality of This Study: This study provides a detailed analysis of farming inputs and their impact on rice productivity in Cambodia, emphasizing the role of land size, seed quality, and chemical inputs. It highlights the need for sustainable practices, such as organic fertilizers, and calls for stronger government and NGO support in agricultural policy and technical assistance. Future research could explore the impact of Good Agricultural Practices (GAP) on rice yield and quality.